Translation Quality of Motivational Expressions in Children’s Stories Provided by Storyweaver - Putri, Silfia Andesta; Nababan, M. R.; Santosa, Riyadi (Universitas Muhammadiyah Semarang, 2024)
Children’s stories and its translation always contain some positive messages that can be delivered in some ways, one of the ways is by motivational expressions in the story. Nowadays, there are so many resources to access children’s stories on the internet, one of online platforms that provided free children’s stories and its translation is Storyweaver. Indonesian stories in this platform are available in translation version from English stories, so it is important to see the transfer quality of motivation’s messages from English as the source text to Indonesian as the target text. The method of this research is descriptive qualitative. 25 children’s stories at level 4 on Storyweaver are selected as research location. Motivational expressions are identified by five types of motivations and the translation quality is assessed by accuracy, acceptability, and readability aspects. Focus Group Discussion (FGD) with three experts is conducted to assess the accuracy and acceptability. The readability is assessed by children who fulfil target reader’s criteria. The result of this study shows; 1) Identified is the most type of motivation found in the stories; 2) Translation of motivational expressions in children’s stories is mostly at a high level of accuracy, acceptability and readability. Nevertheless, there are some data that have medium or low quality because it is translated with unsuitable translation techniques and some data have medium and low readability because the used of unfamiliar terms.